The paradoxical effects of professional stereotypes on the quality of care by interprofessional teams: The contingent effects of team faultlines, team stereotypes, and championship behaviors - Sheffer Hilel, Galia; Drach-Zahavy, Anat; Endevelt, Ronit (Frontiers in Psychology, 2023)
Background Despite calls for interprofessional teamwork to ensure quality care in healthcare settings, interprofessional teams do not always perform effectively. There is evidence that professional stereotypes inhibit effective interprofessional teamwork, but they haven’t been explored as a phenomenon that impacts team’s performance and quality of care. Objectives To focus on professional stereotypes emerging in interprofessional teams and examine the contingency effects of interprofessional team’s faultlines, professional stereotypes, and leader’s championship behaviors on team’s quality of care. Methods A cross-sectional nested sample of 59 interprofessional teams and 284 professionals, working in geriatric long-term-care facilities in Israel. Additionally, five to seven of the residents of each facility were randomly sampled to obtain the outcome variable. Data collection employed a multisource (interprofessional team members), multimethod (validated questionnaires and data from residents’ health records) strategy. Results The results indicated that faultlines are not directly harmful to team’s quality of care; instead, they are likely to impact quality of care only when team stereotypes emerge. Furthermore, whereas teams typified by high professional stereotypes require person-oriented championship leadership, for teams typified by low team stereotypes, championship leadership harms the quality of care they provide. Conclusion These findings have implications for handling interprofessional teams. Practically, leaders must be well-educated to better analyze team members’ needs and maintain the appropriate leadership style.